2017
DOI: 10.3390/rs9030191
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Universal Hyperspectral Index to Assess Chlorophyll Content in Deciduous Forests

Abstract: Abstract:The reflectance properties of leaves are influenced by diverse biochemical components including chlorophyll, one of the key indicators related to plant photosynthesis and plant stress. Although a number of hyperspectral indices have been proposed for quantifying leaf chlorophyll concentrations, their applications are largely restricted to where they were developed and can hardly provide satisfactory results in other cases. In this study, universally applicable hyperspectral indices calculated from bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Most previous studies developed spectral indices based on visible bands ranging from 400 to 760 nm, on either original reflectance or derivative value‐based indices (Peng et al., ). This is because chlorophyll strongly absorbs light at blue (400–500 nm) and red (600–700 nm) regions, and does not include light in the green, orange (500–600 nm), and near‐infrared regions (Houborg et al., ; Beck et al., ; Sonobe & Wang, ). Wider spectra may capture more information of leaf physiological status.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies developed spectral indices based on visible bands ranging from 400 to 760 nm, on either original reflectance or derivative value‐based indices (Peng et al., ). This is because chlorophyll strongly absorbs light at blue (400–500 nm) and red (600–700 nm) regions, and does not include light in the green, orange (500–600 nm), and near‐infrared regions (Houborg et al., ; Beck et al., ; Sonobe & Wang, ). Wider spectra may capture more information of leaf physiological status.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that the outputs from these instruments can be obscured depending on the leaf thickness, as it affects light transmission and scattering [20]. Hyperspectral remote sensing, which mainly concentrates on visible-near infrared (400-1000 nm) light and sometimes contains short-wave infrared ranges (1000-2500 nm), offers some alternative methods to monitor biochemical properties such as chl [21][22][23][24]. Besides the biochemical properties, some narrow wavebands possess high sensitivity to subtle changes in plants caused by stress or diseases, effectively detecting various stress or disease indicators [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The study site is located at Nakagawane forest (138 o 06′ E, 35 o 04′ N) ( Figure 1), one of the research forests of Shizuoka University, Japan [53]. This research site has a typical alpine cold-temperate climate with a mean annual air temperature of 16°C and a mean annual precipitation of approximately 2500 mm [54], and an elevation from 390 to 1560 m.…”
Section: Study Sitementioning
confidence: 99%